2023
DOI: 10.1093/jhered/esad007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architectures of postmating isolation and morphology of two highly diverged rockfishes (genusSebastes)

Abstract: Postmating isolation is thought to be an important driver of the late stages of speciation. However, relatively little is empirically known about the process compared to other isolating mechanisms that drive the early stages of speciation, especially in non-model organisms. We characterized the genetic architecture of postmating isolation between two rockfishes, Sebastes schlegelii and S. trivittatus, whose reproductive isolation is complete. We examined transmission ratio distortion (TRD) patterns of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…It is well accepted that phenotypic traits are important determinants of commercial traits (especially in weight production) and are subject to natural selection and sex differences [30][31][32][33][34][35]. In this study, high CVs of BM and STM were observed in females, and high CVs of SWH and STM were observed in males, indicating that STM could be an important trait with greater selection potential in both female and male selective breeding of the whelk.…”
Section: Discussionmentioning
confidence: 50%
“…It is well accepted that phenotypic traits are important determinants of commercial traits (especially in weight production) and are subject to natural selection and sex differences [30][31][32][33][34][35]. In this study, high CVs of BM and STM were observed in females, and high CVs of SWH and STM were observed in males, indicating that STM could be an important trait with greater selection potential in both female and male selective breeding of the whelk.…”
Section: Discussionmentioning
confidence: 50%